การวิเคราะห์และควบคุมปัจจัยคุณภาพ ที่มีผลกระทบต่อการพ่นสีรถยนต์ - สุวิทย์ กล่ำเพ็ง (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this thesis is appointing and controlling the automotive painting quality factors by using analysis form all problem in process of automotive painting. And to pick and choose define priority first and second problem. The first problem is Dust and Anything Dirty in color film and second problem is Color Mottling after that to solve this two problem by using Causes and Effect Diagrams is quality tool. After that, define cause of problem with be to solve problem by using Brain Storming method. Begin solve problem by using quality tool (SQC) is Check sheet, Graph, Pareto Diagrams and Design of Experiment. After that, follow and evaluate data for solved problem by evaluate data five months, since March 00 to Juiy’00 is compare before and after solved problem. This thesis will be solve high priority problem to analyze percent of defect in automotive painting. After the corrective action is made, defect of paint decrease continuously from last month before improvement from 10.88 defect per unit to 6.22 defect per unit of last month after improvement Dust and Anything Dirty in color film problem defect percent decrease continuously from last month before improvement from 3.34 % to 1.53 % of last month after improvement and Color Mottling problem NG percent decrease continuously from last month before improvement from 1.56 % to 0.28 % of last month after improvement After solve problem until finish afterward fix is regularly work continuously and other cause to point out trend in future.